Intraspecific venom variation in southern African scorpion species of the genera Parabuthus, Uroplectes and Opistophthalmus (Scorpiones: Buthidae, Scorpionidae). (15th March 2018) - Schaffrath, Stephan; Prendini, Lorenzo; Predel, Reinhard
Abstract: Scorpion venoms comprise cocktails of proteins, peptides, and other molecules used for immobilizing prey and deterring predators. The composition and efficacy of scorpion venoms appears to be taxon-specific due to a coevolutionary arms race with prey and predators that adapt at the molecular level. The taxon-specific components of scorpion venoms can be used as barcodes for species identification if the amount of intraspecific variation is low and the analytical method is fast, inexpensive and reliable. The present study assessed the extent of intraspecific variation in newly regenerated venom collected in the field from geographically separated populations of four southern African scorpion species: three buthids, Parabuthus granulatus (Ehrenberg, 1831), Uroplectes otjimbinguensis (Karsch, 1879), and Uroplectes planimanus (Karsch, 1879), and one scorpionid, Opistophthalmus carinatus (Peters, 1861). Although ion signal patterns were generally similar among venom samples of conspecific individuals from different populations, MALDI-TOF mass spectra in the mass range m/z 700–10, 000 revealed only a few ion signals that were identical suggesting that species identification based on simple venom mass fingerprints (MFPs) will be more reliable if databases contain data from multiple populations. In general, hierarchical cluster analysis (HCA) of the ion signals in mass spectra was more reliable for species identification than counts of mass-identical substances in MFPs. The statistical approach revealed conclusive information about intraspecific diversity. In combination with a comprehensive database of MALDI-TOF mass spectra in reflectron mode, HCA may offer a method for rapid species identification based on venom MFPs. Highlights: Venom samples of 60 individuals from different populations of four southern African scorpion species were analyzed. Due to high intraspecific variation, venom fingerprinting revealed only a few potentially species-specific components. Conclusive information about population-specific diversity was obtained by hierarchical clustering analyses. Hierarchical clustering enabled samples to be unambiguously identified to species.